Marketing strategies for artisan cheeses according to the type of market based on a systematic review - Patiño Delgado, América Lina; Cervantes Escoto, Fernando; Espinoza Ortega, Angélica; Cesín Vargas, Alfredo; Palacios Rangel, María Isabel (Textual, 2021)
This study analyzes the strategic marketing activities based on studies related to artisan cheeses made in Mexico and in other countries during the last decade. This analysis was carried out by means of a systematic review to determine whether there is relation between the strategic activities carried out and the target market of artisan cheeses. The strategic activities found were classified into six categories: collaboration, innovation, channel selection, differentiation, survival, and relationship with the consumer. It is concluded that there is a clear correspondence between the strategic actions and the target market.